Freeze-Out Mergers - Dalkır, Elif; Dalkır, Mehmet; Levit, Doron (Review of Financial Studies, 2019)
Abstract Do freeze-out mergers mitigate the free-rider problem of corporate takeovers? We study this question in a tender offer model with finitely many shareholders. Under a freeze-out merger, minority shareholders expect to receive the original offer price whether or not they tender their shares. We show that the ability to freeze out shareholders increases the raider’s expected profit. However, as the number of shareholders gets arbitrarily large, the raider’s expected profit in equilibrium converges to zero for any freeze-out clause with an ownership threshold that is strictly above simple majority. In this sense, freeze-out mergers do not solve the free-rider problem. Received September 17, 2016; editorial decision June 3, 2018 by Editor Francesca Cornelli.